Reconciliation with oneself and with others: From approach to model - Nikolić-Ristanović Vesna; Srna Jelena (Temida, 2010)
The paper intends to present the approach to dealing with war and its consequences which was developed within Victimology Society of Serbia over the last five years, in the framework of Association Joint Action for Truth and Reconciliation (ZAIP). First, the short review of the Association and the process through which ZAIP approach to dealing with a past was developed is presented. Then, the detailed description of the approach itself, with identification of its most important specificities, is presented. In the conclusion, next steps, aimed at development of the model of reconciliation which will have the basis in ZAIP approach and which will be appropriate to social context of Serbia and its surrounding, are suggested.